How does mothering look like: a multidimensional approach to maternal cognitive representations - Camilo, C. (2019)
From a cognitive information processing perspective, parents’ cognitive schemas strongly influence the way they perceive and act towards their children. In order to explore how maternal cognitive representations about parenting are organized in a multi-dimensional space, mothers referred to child protection services and mothers with no such reference completed a free description task of maternal attributes and a sorting task of those attributes according to their probability of co-occurrence in the same mother. Overall, the results suggest that maladaptive parenting seems to be associated with less positive parental schemata, higher schemata rigidity and higher external attributions regarding parenting. Using MDS to represent the structure and content of maternal schemata constitutes an innovative contribution to the parenting domain with potential applications. These conceptual maps representing maternal schemata that shape parental responses in childrearing situations can be used as theoretical frameworks to develop empirically based guidelines for intervention work with maltreating parents.